Voices of War in Children’s Literature Against the Background of Conflict in the Gaza Stri - Lea, Baratz (International Journal of Social Science Research, 2024)
This article aims to review children’s books written about children living in the Israeli Gaza region under the shadow of a continuous security threats. Since 2001, five rounds of fighting have taken place. A content analysis methodology was adopted to examine the social and cultural processes of the adult narrators, their attitudes towards their Arab neighbours and the voice of the child who dreams about quiet days and peace. Two main motifs emerged: the first represents the ‘sounds of war’ and the second the motif of peace. The themes reveal a dimension of values, beliefs, symbols and myths, conceptualising the enemy in semantic submission to the concept of war and peace. These children’s books allow young readers to examine complex realities through the experiences of literary characters and engage in cognitive and emotional processing without being directly exposed to the experiences.